Frailty, depression, and quality of life: a study with elderly caregivers - Melo,Letícia Alves de (2020)
ABSTRACT Objective: to analyze the relationship between frailty, depressive symptoms, and quality of life of elderly caregivers of other elderly living in high social vulnerability. Methods: a descriptive, correlational and cross-sectional study conducted with 40 elderly caregivers. A questionnaire to characterize elderly caregivers, the Fried frailty phenotype, the Geriatric Depression Scale (to screen depressive symptoms) and the Short-Form 6 Dimension (to assess quality of life) were used. For data analysis, Student’s t-test, ANOVA, Pearson’s χ2 and Fisher’s exact test were used. Results: most were pre-frail (52.5%) and had no evidence of depressive symptoms (57.5%). They presented, on average, a score of 0.76 (±0.1) in relation to quality of life. Statistical significance was observed between the average scores of quality of life with depressive symptoms (p=0.012) and frailty level (p=0.004). Conclusion: frail elderly caregivers with depressive symptoms had a worse perception of quality of life.